Inhibitors of the Cdc34 acidic loop: A computational investigation integrating molecular dynamics, virtual screening and docking approaches. Issue 1 (9th May 2014) - Arrigoni, Alberto; Bertini, Luca; De Gioia, Luca; Papaleo, Elena
Abstract : Here, we carried out a computational study based on molecular dynamics, virtual screening and docking to identify potential inhibitory compounds of Cdc34, modulating the acidic loop conformation. The molecules identified in this study have been designed to act as molecular hinges that can bind the acidic loop in its closed conformation, thus inhibiting the Cdc34‐mediated ubiquitination cascade at the ubiquitin‐charging step. In particular, we proposed a pharmacophore model featuring two amino groups in the central part of the model and two lateral aromatic chains, which respectively establish electrostatic interactions with the acidic loop (Asp 108 and Glu 109) and a hydrogen bond with Ser 139, which is one of the key residues for Cdc34 activity. Abstract : Cdc34 is an E2 enzyme involved in protein ubiquitination and associated with some cancers. Cdc34 activity is modulated by phosphorylation‐induced conformational changes of the acidic loop. We used computational approaches to identify potential inhibitory compounds for Cdc34. These inhibitors as molecular hinges stabilizing the acid loop in its inactive, closed conformation.